2017
DOI: 10.21053/ceo.2016.01354
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Improvement in A/J Mice via the Mouse Nerve Growth Factor

Abstract: Objectives To investigate the otoprotective effects of mouse nerve growth factor (mNGF) in A/J mice.Methods The mice at postnatal day 7 (P7) were randomly separated into a mNGF treated group (mNGF group) and a distilled water (for injection) treated group (control group). The mNGF dissolved in distilled water or distilled water alone was given to the mice once every other day from P7 by intramuscular injection in the hips. The otoprotective effects of mNGF in A/J mice were observed in a time course manner. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Several growth factors prevent degeneration of cochlear neurons, such as NGF [ 151 ], neurotrophic factor-3 (NT-3) [ 152 ], which have been shown to prevent ototoxic drug-induced hearing loss, NIHL and ARHL. However, some studies have found that the presence of hypertension and delayed treatment are negative factors related to the effectiveness of NGF treatment [ 153 ].…”
Section: Pathophysiological Mechanisms and Treatment Strategies Of Arhlmentioning
confidence: 99%
“…Several growth factors prevent degeneration of cochlear neurons, such as NGF [ 151 ], neurotrophic factor-3 (NT-3) [ 152 ], which have been shown to prevent ototoxic drug-induced hearing loss, NIHL and ARHL. However, some studies have found that the presence of hypertension and delayed treatment are negative factors related to the effectiveness of NGF treatment [ 153 ].…”
Section: Pathophysiological Mechanisms and Treatment Strategies Of Arhlmentioning
confidence: 99%
“…An imbalance of neurotrophic factors and their receptors has been reported for both AD and ARHL. In this context, nerve growth factor (NGF), GDNF and BDNF stand out [ 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. The identified neurotrophic factors affected have been shown to have meaningful implications in the frame of neuronal degeneration processes.…”
Section: Neurotrophic Factors At the Interface Of Ad Pathophysiology ...mentioning
confidence: 99%
“…These therapies appear to be promising to protect or promote the regeneration of both hair cells and SGNs, thus regenerating or even preventing deafness of the mammalian inner ear [ 130 ]; meanwhile, they positively affect AD. However, their safety and efficacy in clinical studies are not yet proven [ 125 , 131 , 132 ]. Further future research and randomized clinical trials are warranted to examine and foster these implications of treatment for cognition and ARHL on a more profound level.…”
Section: Neurotrophic Factors At the Interface Of Ad Pathophysiology ...mentioning
confidence: 99%
“…Furthermore, other neurotrophic factors were tested in animal models of hearing loss. For example, NGF or NT3 application prevents the OHC loss in mouse models of early-onset progressive hearing loss (78)(79)(80).…”
Section: Attenuation Of Outer Hair Cell Loss Without Functional Effec...mentioning
confidence: 99%